2017
DOI: 10.1080/15384101.2017.1327490
|View full text |Cite
|
Sign up to set email alerts
|

Nitidine chloride inhibited the expression of S phase kinase-associated protein 2 in ovarian cancer cells

Abstract: Nitidine chloride (NC) has been reported to exert its anti-tumor activity in various types of human cancers. However, the molecular mechanism of NC-mediated tumor suppressive function is largely unclear. In the current study, we used several approaches such as MTT, FACS, RT-PCR, Western blotting analysis, invasion assay, transfection, to explore the molecular basis of NC-triggered anti-cancer activity. We found that NC inhibited cell growth, induced cell apoptosis, caused cell cycle arrest in ovarian cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Skp2 as an oncoprotein is the key adaptor of the SCF type of E3 ligase [35][36][37]. NC was reported to inhibit the Skp2 level in OC cells, while Skp2 upregulation abolished NC-induced antitumor property [38]. Thus, suppression of Skp2 expression level by NC might be a useful approach for management of OC patients [38].…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Skp2 as an oncoprotein is the key adaptor of the SCF type of E3 ligase [35][36][37]. NC was reported to inhibit the Skp2 level in OC cells, while Skp2 upregulation abolished NC-induced antitumor property [38]. Thus, suppression of Skp2 expression level by NC might be a useful approach for management of OC patients [38].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…NC was reported to inhibit the Skp2 level in OC cells, while Skp2 upregulation abolished NC-induced antitumor property [38]. Thus, suppression of Skp2 expression level by NC might be a useful approach for management of OC patients [38]. There is one study showing that NC blocked cell migratory and invasive activity through downregulation of MMP-2 as well as MMP-9 via suppression of ERK pathway in OC cells [39].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Recently, compound 25, a novel Skp2 inhibitor, was shown to exhibit potent antitumor activities and to cooperate with chemotherapeutic agents to suppress cancer cell survival ( 61 ). Several natural compounds have been reported to exert their antitumor activities via the inhibition of Skp2 expression in human cancers ( 62 64 ). It is important to note that natural compounds do not specifically inhibit Skp2.…”
Section: Discussionmentioning
confidence: 99%
“…NC, one of the natural products, has also been studied to play an important role in the inhibition of cell proliferation in various cancers. For examples, NC triggers apoptosis and cell cycle arrest in ovarian cancer cells via suppression of S phase kinase‐associated protein 2 (Skp2) and inhibits malignant behavior of the human glioblastoma cells by targeting PI3K/AKT/mTOR signaling pathway . Zhai et al have reported the apoptotic activity of NC in colorectal cancer cells by regulating ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%